Early dopaminergic replacement treatment initiation benefits motor symptoms in patients with Parkinson's disease - Li, Xin; Dong, Zhao-ying; Dong, Meng; Chen, Lei (Frontiers in Human Neuroscience, 2024)
BACKGROUND: Parkinson's disease (PD) generally progresses slowly, but it is controversial whether delaying treatment accelerates the progression. OBJECTIVE: Determine the correlation between the time of dopaminergic replacement treatment initiation and the severity of clinical symptoms in PD, including motor and non-motor symptoms.METHODS: PD patients were divided between 155 people who were diagnosed de novo and 165 PD patients receiving dopamine replacement therapy. Basic patient characteristics included gender, age, age at onset, disease duration, and the time of dopaminergic replacement treatment initiation. We used MDS-UPDRS scores to evaluate the severity of motor symptoms and other scales to assess the severity of non-motor symptoms such as cognition, mood, sleep, and quality of life.The mean time between symptom onset and the initiation of drug treatment was 31.0(22.5) months. After adjusting for age, sex, age at onset, and disease duration, we found that the Unified Parkinson's Disease Rating Scale (UPDRS)-III score increased faster in the de novo group with a similar disease duration (F=8.7, p=0.0034) than the treatment group. The cumulative incidence of progression to H-Y score 3 in de novo PD group over disease duration was 39.7% in 50months and 92.2% in 100 months, while in treated group such cumulative incidence was 15.5% in 50 months, 51.4% in 100 months and 81.5% in 150 months. The cumulative incidence of patients in the de novo PD group was higher than that in the treated group(p=0.001), suggesting that untreated patients were more likely to progress to the advanced stages. Symptoms onset, the time between symptom onset and treatment initiation, age, sex, and disease duration explained 28.95% of the total variation in the UPDRS-III score for motor symptoms. In drug-naïve patients, the time between symptom onset and treatment initiation explained 20.1% of the total variation in the UPDRS-III score for motor symptoms (t=6.15, p<0.001).CONCLUSIONS: These data in our study showed that early dopaminergic replacement treatment have played a positive role in PD patients, while dopaminergic replacement delayed treatment might be detrimental to motor symptoms and nonmotor state of PD patient. Recognizing early stage symptoms of PD and early diagnosis are of great significance to treatment.